Anticholinergic effect of resveratrol with vitamin E on scopolamine-induced Alzheimer’s disease in rats: Mechanistic approach to prevent inflammation - Foudah, Ahmed I.; Devi, Sushma; Alam, Aftab; Salkini, Mohammad Ayman; Ross, Samir A. (Frontiers in Pharmacology, 2023)
The most common form of dementia, Alzheimer's disease (AD), is characterized by gradual declines in cognitive abilities and behavior. It is caused by a combination of factors, including amyloid-β (Aβ) accumulation, acetylcholine (ACh) loss, oxidative stress, and inflammation. Phenolic compounds have a variety of health benefits, including antioxidant activities. Thus, the purpose of this study was to investigate how resveratrol (RES) alone and in combination with vitamin E affected rats with AD using scopolamine (SCO). Animals are categorized into groups; (i) control, (ii) SCO (1 mg/kg i.p.), (iii) SCO + donepezil, (iv) SCO + RES (50 mg/kg, p.o.), (v) SCO + RES (75 mg/kg, p.o.), (vi) SCO + RES (50 mg/kg + vitamin E 1mg/kg, p.o.) for 17 days. In rats, studied behavioural (NOR and EPM) and biochemical characteristics. In addition, brain histopathology was examined to investigate any damage to the hippocampus and neuroprotection. SCO-induced changes in acetylcholinesterase, protein carbonyl, and TNF-α improved after resveratrol treatment. RES increased antioxidant levels, decreased SCO-induced lipid peroxidation, and reversed SCO-mediated changes compared with the drug donepezil. The results indicated that RES and vitamin E had nootropic action in the NOR and EPM tests, measured by the recognition index and the inflection ratio. This study supports the efficacy of RES as a preventive and treatment agent for AD. Vitamin E showed a synergistic effect on RES, which helps in managing cognitive impairment AD.